Carbon Dots as New Generation Materials for Nanothermometer: Review - Lazo Jazaa Mohammed; Khalid M. Omer (Nanoscale Research Letters, 2020)
Abstract Highly sensitive non-contact mode temperature sensing is substantial for studying fundamental chemical reactions, biological processes, and applications in medical diagnostics. Nanoscale-based thermometers are guaranteeing non-invasive probes for sensitive and precise temperature sensing with subcellular resolution. Fluorescence-based temperature sensors have shown great capacity since they operate as “non-contact” mode and offer the dual functions of cellular imaging and sensing the temperature at the molecular level. Advancements in nanomaterials and nanotechnology have led to the development of novel sensors, such as nanothermometers (novel temperature-sensing materials with a high spatial resolution at the nanoscale). Such nanothermometers have been developed using different platforms such as fluorescent proteins, organic compounds, metal nanoparticles, rare-earth-doped nanoparticles, and semiconductor quantum dots. Carbon dots (CDs) have attracted interest in many research fields because of outstanding properties such as strong fluorescence, photobleaching resistance, chemical stability, low-cost precursors, low toxicity, and biocompatibility. Recent reports showed the thermal-sensing behavior of some CDs that make them an alternative to other nanomaterials-based thermometers. This kind of luminescent-based thermometer is promising for nanocavity temperature sensing and thermal mapping to grasp a better understanding of biological processes. With CDs still in its early stages as nanoscale-based material for thermal sensing, in this review, we provide a comprehensive understanding of this novel nanothermometer, methods of functionalization to enhance thermal sensitivity and resolution, and mechanism of the thermal sensing behavior.